The Effect of Financial Literacy,Financial Inclusion, Capital Access and Digital Payment on The Financial Performance of Convection UMKM Registered with The Cooperative, UMKM and Trade Service of Tegal Regency - Ghina Sari, Awlia; Indriasih, Dewi; Fanani, Baihaqi; Mubarok, Abdulloh; Firmansyah, Fahmi; Puji Astutie, Yanti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The data used in this study are secondary data obtained from the Tegal Regency Cooperatives, SMEs, and Trade Office. This research employs a quantitative approach, with sampling conducted using the proportional sampling method, resulting in a total of 153 respondents. Based on the results of the analysis, it can be concluded that financial literacy does not significantly influence the financial performance of convection MSMEs in Tegal Regency. However, financial inclusion, access to capital, and digital payments were found to have a significant positive effect on the financial performance of these MSMEs.